Are step-parents really mean: a view from pedagogy and evolutionary psychology - Dadić, Katarina; Pušić, Bruno (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2017)
In many cultures there are stereotypes about the “cruelty” of step-parents towards their step-children. These stereotypes usually arise (1) from ambiguous roles of step-parents in the family, and (2) the predominantly negative attitude of children towards their biological parents re-marrying . In this paper, we discuss whether these stereotypes have any foothold in real life. We used the pedagogical approach and the approach of evolutionary psychology in our research. Our paper discusses in detail the existing stereotypes of step-parents. The goal is to determine whether children living with one biological parent and one step-parent actually live in unfavourable family conditions when compared to children living with both biological parents. Furthermore, a detailed review of recent pedagogical research and research from evolutionary psychology about step-parents has contributed to the pedagogical evaluation of this problem in order to determine (a) why are the existing stereotypes of step-parents and their relationships with their step-children a challenge for modern pedagogy? and (b) how can modern pedagogy respond to current problems?
Keywords: step-mother; step-father; child; family; pedagogy; evolutionary psychology; stereotypes